Endogenous reactive oxygen species burst induced and spatiotemporally controlled multiple drug release by traceable nanoparticles for enhancing antitumor efficacy. (4th June 2021) - Wang, Ning; Liu, Chenyu; Yao, Weihe; Zhou, Hengjun; Yu, Simiao; Chen, Hailiang; Qiao, Weihong
Abstract : Reactive oxygen species (ROS) are not only used as a therapeutic reagent in chemodynamic therapy (CDT), to stimulate the release of drugs, they can also be used to achieve a combined effect of CDT and chemotherapy to enhance anticancer effects. Abstract : Reactive oxygen species (ROS) are not only used as a therapeutic reagent in chemodynamic therapy (CDT), to stimulate the release of antineoplastic drugs, they can also be used to achieve a combined effect of CDT and chemotherapy to enhance anticancer effects. Herein, we synthesized a pH-responsive prodrug (PEG 2k -NH-N-DOX ), ROS-responsive prodrug (PEG 2k -S-S-CPT-ROS ), organic CDT agents (TPP-PEG 2k -LND, TPP-PEG 2k -TOS), and T1-enhanced magnetic resonance imaging contrast agents (Gd-DTPA-N16-16), and used them to encapsulate combrestatinA4 (CA4) to prepare traceable pH/ROS dual-responsive multifunctional nanoparticles (TLDCAG NPs) with endogenous ROS burst and spatiotemporally controlled multiple drug release ability. Firstly, TLDCAG NPs were accumulated in the tumor cell microenvironment via an enhanced permeability and retention (EPR) effect. Secondly, CA4 was released and specifically destroyed angiogenesis to facilitate the interaction between the tumor and the remaining TLDCG NPs. After accumulating in tumor cells, the TLDCG NPs could be destroyed under acidic conditions to quickly release doxorubicin (DOX), TPP-PEG 2k -LND, and TPP-PEG 2k -TOS . Thirdly, TPP-PEG 2k -LND and TPP-PEG 2k -TOS quickly targeted mitochondria, induced endogenous ROS bursts, reduced the mitochondrial membrane potential, and induced tumor cell apoptosis. Endogenous ROS can not only be used as a therapeutic reagent for CDT, but also can cut off the thioketal bond in PEG 2k -S-S-CPT-ROS and release camptothecin (CPT). Finally, TLDCAG NPs were traced by magnetic resonance imaging (MRI). Furthermore, in vitro and vivo results indicate that the TLDCAG NPs have vigorous antitumor activity and negligible systemic toxicity. Therefore, the TLDCAG NPs provide an efficient strategy for enhancing antitumor efficacy.